Catalytic effects of CaO, Al2O3, Fe2O3, and red mud on Pteris vittata combustion: Emission, kinetic and ash conversion patterns. (10th April 2020) - Song, Yueyao; Hu, Jinwen; Liu, Jingyong; Evrendilek, Fatih; Buyukada, Musa
Abstract: Catalytic effects of red mud (RM), calcium oxide (CaO), aluminum trioxide (Al2 O3 ), and ferric oxide (Fe2 O3 ) were quantified on the combustion, emission and ash characteristics of aboveground (PA) and belowground (PB) biomass of Pteris vittata using thermogravimetric, Fourier transform infrared, X-ray fluorescence and FactSage analyses. CaO affected the specific formation pathways of tar species and inhibited the CO2, HCN and SO2 emissions. Fe2 O3 shortened the initial release time of the emissions. Al2 O3 inhibited the final NO emission but did not control the N-containing products. RM catalyzed the combustion by suppressing the emissions. The enthalpy of PA was catalytically enhanced in the following order: CaO > RM > Fe2 O3 > Al2 O3 . Only Fe2 O3 increased the enthalpy of PB. The stationary index value of PB declined with the catalysts. The comprehensive combustion index of PA was high at 20 ° C/min. Al2 O3 reduced the risks of slagging, and fouling for PA and PB, while RM exerted a more pronounced effect on PA than PB. The fusion of low-melting point minerals accelerated the mass and heat transfers, and the ash melting. Activation energy was reduced by 275.99% with RM and by 119.82 and 115.81% with Al2 O3, and Fe2 O3 for PA, respectively. Our results pave the way for cleaner and sustainable production strategies with the catalytic biomass combustion. Graphical abstract: Image 1 Highlights: Pteris vittata combustion was catalyzed with red mud, CaO, Al2 O3 and Fe2 O3 . CaO inhibited CO2, HCN and SO2 emissions. Activation energy declined with red mud for PB and with Al2 O3 and Fe2 O3 for PA. Al2 O3 significantly reduced the fouling risk of P. vittata. Red mud led to an improved combustion efficiency and a cleaner energy production.